Design and synthesis of doublecortin-like kinase 1 inhibitors and their bioactivity evaluation - Pengming Pan; Dengbo Ji; Zhongjun Li; Xiangbao Meng (Taylor & Francis Group, 2024)
AbstractDoublecortin-like kinase 1 (DCLK) is a microtubule-associated serine/threonine kinase that is upregulated in a wide range of cancers and is believed to be related to tumour growth and development. Upregulated DCLK1 has been used to identify patients at high risk of cancer progression and tumours with chemotherapy-resistance. Moreover, DCLK1 has been identified as a cancer stem cell (CSC) biomarker in various cancers, which has received considerable attention recently. Herein, a series of DCLK1 inhibitors were prepared based on the previously reported XMD8-92 structure. Among all the synthesised compounds, D1, D2, D6, D7, D8, D12, D14, and D15 showed higher DCLK1 inhibitory activities (IC50 40-74 nM) than XMD8-92 (IC50 161 nM). Compounds D1 and D2 were selective DCLK1 inhibitors as they showed a rather weak inhibitory effect on LRRK2. The antiproliferative activities of these compounds were also preliminarily evaluated. The structure-activity relationship revealed by our compounds provides useful guidance for the further development of DCLK1 inhibitors.